Party competition and dual accountability in multi-level systems. Issue 4 (1st October 2020) - Baumann, Markus; Ecker, Alejandro; Gross, Martin
ABSTRACT: Sub-national self-governance is on the rise across European democracies. This increasing decentralization changes party competition in multi-level governance systems, and has broad implications for voters' ability to assign political responsibility and to hold politicians accountable. Regarding the interplay between party competition and dual accountability – that is, the attribution of accountability to the relevant level – in multi-level governance systems, we propose to distinguish conceptually between an electoral and a governmental arena. Whereas dual accountability in the electoral arena is challenged by varying degrees of party system nationalization, the governmental arena is characterized by a trade-off between the wish for clear-cut dual accountability and the need for political stability. We discuss these challenges in detail and link the various contributions in this special issue to these challenges. We add to the existing literature that increasingly deals with the theoretical and empirical challenges of electoral accountability in ever more institutionally complex systems of multi-level governance.